(untitled) (Research, Society and Development, 2025)
Objective: To outline the epidemiological profile of Zika cases in the state of Maranhão from 2019 to 2024. Methodology: This research is classified as a retrospective epidemiological study with a quantitative approach. The research was based on secondary data from records provided by the Notifiable Diseases Information System (SINAN), linked to the Department of Informatics of the Unified Health System (DATASUS). Results: Within this time frame, 5,790 cases of Zika virus were reported, with a highlight on the years 2022 and 2023, which presented high peaks in notifications. Regarding the distribution of Zika virus cases in the municipalities of the state of Maranhão, it was observed that São Luís, the state capital, registered the highest number of notifications, with 42.7% of the total cases. There was a predominance of females with 57.3% of cases, as well as of mixed race (76.1%). The predominant age group was 20 to 39 years (28.7%). Regarding education, complete secondary education predominated (24.3%). Laboratory testing was the predominant diagnostic criterion, accounting for 76.9% of cases. In terms of classification, the highest number of discarded cases was 77.8%. In terms of outcome, 80.3% of cases resulted in recovery. Among the reported cases, there were at least one pregnant woman; of the 5,790 (100.0%), 149 (2.6%) were pregnant, and when the trimester of pregnancy was analyzed, 38.9% stated they were in the second trimester. Conclusion: Therefore, identifying the epidemiological profile of cases helps managers and health professionals in planning and improving care, as well as facilitating problem-solving.